Antibiotic effects of aqueous extract of honeybee propolis against Xanthomonas vasicola P.V. Musacearum - Fiaboe, K.K.M.; Beed, Fenton D.; Mwangi, M.; Kubiriba, Jerome; Tushemereirwe, Wilberforce K. (2008)
Xanthomonas vasicola p.v. mucasearum (Xvm) is the causal agent of banana bacterial wilt which is currently constraining banana production in Eastern Africa. One mode of transmission is by insect vectors and studies in Uganda have shown that drosophilids, honey and stingless bees are of particular importance. It is not yet known if bee hives consist pools for Xvm multiplication and spread or if the propolis’ antimicrobial defense at hives entrance can eliminate Xvm. The present study aimed at investigating the presence of antibiotic compounds andor organisms contained in water extract of propolis that can be effective against Xvm. Fresh propolis from hives was soaked in water for 15 days at 37oC and afterwards filtered through a Whatman® filter paper No. 1 (185mm diameter). Two types of extract solutions were prepared: a) non sterile propolis extract solution (NSP) and b) sterile-filtered extract solution (SP), prepared by filtering again through a Whatman® sterile filter to remove all living organisms (25mm diameter and 0.2 µm pore size). Each extract was separately mixed with Xvm cell suspension (2 x 106 CFUml) at a ratio of 1:4 (vv, extractXvm suspension) and 100 µl was added to both non-selective medium (YPGA) and selective medium (SM) (containing 5-fluorouracil and Cephalexin) in 9cm Petri dishes The control consisted of Xvm cell suspension mixed with sterile water in place of the propolis extract. Bacterial growth was evaluated after 72hrs using a scale varying from 0 to 5, based on colony coverage of the medium surface. Growth of Xvm on YPGA was not significantly different between the control and sterilized extract (mean growth scores of 4.9 ± 0.1 and 4.8 ± 0.1, respectively). However the non sterile extract completely inhibited the growth of Xvm colonies on both YPGA and SM media. A, as yet unidentified, gram positive bacteria (PB) was obtained from NSP with mean growth scores of 5.0 ± 0.1 on both media. Subsequent studies consisted of growing a pure culture of PB on YPGA media at the same time as Xvm with eight spots of Xvm (2mm diameter each) surrounded by nine spots of PB. After 72hrs, the mean growth scores were 0.1 ± 0.1 and 4.9 ± 0.1 for Xvm and PB, respectively. The Xvm colonies showed initial convex growth morphologies when adjacent to PB colonies and were then killed. The present results demonstrate the presence of at least one antagonistic bacterial species in the propolis, suggesting possible suppression of Xvm on insect body at hive entrance. These findings warrant further study for possible biocontrol of Xvm.